THE EFFECT OF CALCIUM AND PHOSPHOROUS ON GROWTH, FEED EFFICIENCY, MINERAL CONTENT AND BODY COMPOSITION OF BROWN MARBLED GROUPER (Epinephelus fuscoguttatus) JUVENILE - Zainuddin Zainuddin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2010)
The objectives of this study were to know concentration of calcium (Ca) and posphorus (P) in feed for growth, feed efficiency, proximate composition of the body and mineral content of brown marbled grouper juvenile. The study was conducted in the Center for Brackiswater Aquaculture Development, Takalar with randomized completed design 6 x 3 with the treatment of Ca and P supplement in feed i.e., (A) the supplement of 0 g/kg Ca and 0 g/kg P, (B) the supplement of 6 g/kg Ca and 0 g/kg P, (C) the supplement of 0 g/kg Ca and 6 g/kg P, (D) the supplement of 6 g/kg Ca and 6 g/kg P, (E) the supplement of 12 g/kg Ca and 6 g/kg P, and (F) the supplement of 18 g/kg Ca and 6 g/kg P. The result showed that P supplement with doses of 6 g/kg and Ca of 0 g/kg in feed are significantly affects on relative growth, feed efficiency, proximate composition and mineral content of brown marbled grouper juvenile.Keywords: growth, feed efficiency, proximate composition, brown marbled grouper juvenile